Powers - Special Cases

Powers of negative numbers

When we have an exponent on a negative number, we can get a positive result or a negative result.
We will know this based on the exponent – whether it is even or odd.

Powers with exponent \(0\)

Any number with an exponent of 00 will be equal to 11. (Except for 00)
No matter which number we raise to the power of 00, we will always get a result of 1.

Powers with negative integer exponents

In an exercise where we have a negative exponent, we turn the term into a fraction where:
the numerator will be 11 and in the denominator, the base of the exponent with the positive exponent.

Practice Powers - special cases

Examples with solutions for Powers - special cases

Exercise #1

192=? 19^{-2}=\text{?}

Video Solution

Step-by-Step Solution

In order to solve the exercise, we use the negative exponent rule.

an=1an a^{-n}=\frac{1}{a^n}

We apply the rule to the given exercise:

192=1192 19^{-2}=\frac{1}{19^2}

We can then continue and calculate the exponent.

1192=1361 \frac{1}{19^2}=\frac{1}{361}

Answer

1361 \frac{1}{361}

Exercise #2

Which of the following is equivalent to 1000 100^0 ?

Video Solution

Step-by-Step Solution

Let's solve the problem step by step using the Zero Exponent Rule, which states that any non-zero number raised to the power of 0 is equal to 1.


  • Consider the expression: 1000 100^0 .
  • According to the Zero Exponent Rule, if we have any non-zero number, say a a , then a0=1 a^0 = 1 .
  • Here, a=100 a = 100 which is clearly a non-zero number, so following the rule, we find that:
  • 1000=1 100^0 = 1 .

Therefore, the expression 1000 100^0 is equivalent to 1.

Answer

1

Exercise #3

1123=? \frac{1}{12^3}=\text{?}

Video Solution

Step-by-Step Solution

To begin with, we must remind ourselves of the Negative Exponent rule:

an=1an a^{-n}=\frac{1}{a^n} We apply it to the given expression :

1123=123 \frac{1}{12^3}=12^{-3} Therefore, the correct answer is option A.

Answer

123 12^{-3}

Exercise #4

Insert the corresponding expression:

(120)7= \left(\frac{1}{20}\right)^{-7}=

Video Solution

Step-by-Step Solution

To simplify the expression (120)7 \left(\frac{1}{20}\right)^{-7} , we will apply the rule for negative exponents. The key idea is that a negative exponent indicates taking the reciprocal and converting the exponent to a positive:

  • Start with the expression: (120)7 \left(\frac{1}{20}\right)^{-7} .
  • Apply the negative exponent rule: (1a)n=an \left(\frac{1}{a}\right)^{-n} = a^n .
  • For our expression: (120)7 \left(\frac{1}{20}\right)^{-7} becomes 207 20^7 .

Therefore, (120)7 \left(\frac{1}{20}\right)^{-7} simplifies to 207 20^7 .

Thus, the correct answer is 207 20^7 .

Answer

207 20^7

Exercise #5

Insert the corresponding expression:

(160)4= \left(\frac{1}{60}\right)^{-4}=

Video Solution

Step-by-Step Solution

To solve for (160)4 \left(\frac{1}{60}\right)^{-4} , we apply the rule for negative exponents.

Step 1: Use the negative exponent rule: For any non-zero number a a , an=1an a^{-n} = \frac{1}{a^n} . Thus,

(160)4=(601)4 \left(\frac{1}{60}\right)^{-4} = \left(\frac{60}{1}\right)^4 .

Step 2: Simplify (601)4\left(\frac{60}{1}\right)^4 by recognizing the identity 601=60\frac{60}{1} = 60, so it follows that:

(601)4=604 \left(\frac{60}{1}\right)^4 = 60^4 .

Therefore, the simplified expression is 604 60^4 .

The correct answer is 604 60^4

Answer

604 60^4

Exercise #6

Insert the corresponding expression:

152= \frac{1}{5^2}=

Video Solution

Step-by-Step Solution

To solve the given problem, we need to express 152 \frac{1}{5^2} using negative exponents. We'll apply the formula for negative exponents, which is 1an=an \frac{1}{a^n} = a^{-n} :

  • Identify the base and power in the denominator. Here, the base is 5 5 and the power is 2 2 .
  • Apply the inverse formula: 152=52 \frac{1}{5^2} = 5^{-2} .

Thus, the equivalent expression for 152 \frac{1}{5^2} using a negative exponent is 52 5^{-2} .

Answer

52 5^{-2}

Exercise #7

Insert the corresponding expression:

142= \frac{1}{4^2}=

Video Solution

Step-by-Step Solution

To solve the problem of expressing 142\frac{1}{4^2} using powers with negative exponents:

  • Identify the base in the denominator: 4 raised to the power 2.
  • Apply the rule for negative exponents that states 1an=an\frac{1}{a^n} = a^{-n}.
  • Express 142\frac{1}{4^2} as 424^{-2}.

Thus, the expression 142\frac{1}{4^2} can be rewritten as 42 4^{-2} .

Answer

42 4^{-2}

Exercise #8

Insert the corresponding expression:

(13)4= \left(\frac{1}{3}\right)^{-4}=

Video Solution

Step-by-Step Solution

To solve this problem, we'll follow these steps:

  • Step 1: Identify the given expression with a negative exponent.
  • Step 2: Apply the rule for negative exponents, which allows us to convert the expression into a positive exponent form.
  • Step 3: Perform the calculation of the new expression.

Now, let's work through each step:

Step 1: The expression given is (13)4 \left(\frac{1}{3}\right)^{-4} , which involves a negative exponent.

Step 2: According to the exponent rule (ab)n=(ba)n \left(\frac{a}{b}\right)^{-n} = \left(\frac{b}{a}\right)^n , we can rewrite the expression with a positive exponent by inverting the fraction:

(13)4=(31)4=34 \left(\frac{1}{3}\right)^{-4} = \left(\frac{3}{1}\right)^4 = 3^4 .

Step 3: Calculate 34 3^4 .

The calculation 34 3^4 is as follows:

34=3×3×3×3=81 3^4 = 3 \times 3 \times 3 \times 3 = 81 .

However, since the problem specifically asks for the corresponding expression before calculation to numerical form, the answer remains 34 3^4 .

Therefore, the answer to the problem, in terms of an equivalent expression, is 34 3^4 .

Answer

34 3^4

Exercise #9

Insert the corresponding expression:

132= \frac{1}{3^2}=

Video Solution

Step-by-Step Solution

To solve this problem, we'll use the rule of negative exponents:

  • Step 1: Identify that the given expression is 132\frac{1}{3^2}.
  • Step 2: Recognize that 132\frac{1}{3^2} can be rewritten using the negative exponent rule.
  • Step 3: Apply the formula 1an=an\frac{1}{a^n} = a^{-n} to the expression 132\frac{1}{3^2}.

Now, let's work through these steps:

Step 1: We have 132\frac{1}{3^2} where 3 is the base and 2 is the exponent.

Step 2: Using the formula, convert the denominator 323^2 to 323^{-2}.

Step 3: Thus, 132=32\frac{1}{3^2} = 3^{-2}.

Therefore, the solution to the problem is 323^{-2}.

Answer

32 3^{-2}

Exercise #10

Insert the corresponding expression:

167= \frac{1}{6^7}=

Video Solution

Step-by-Step Solution

To solve this problem, we will rewrite the expression 167\frac{1}{6^7} using the rules of exponents:

Step 1: Identify the given fraction.

We start with 167\frac{1}{6^7}, where the base in the denominator is 6, and the exponent is 7.

Step 2: Apply the formula for negative exponents.

The formula an=1ana^{-n} = \frac{1}{a^n} allows us to rewrite a reciprocal power as a negative exponent. This means the expression 167\frac{1}{6^7} can be rewritten as 676^{-7}.

Step 3: Conclude with the answer.

By transforming 167\frac{1}{6^7} to its equivalent form using negative exponents, the expression becomes 676^{-7}.

Therefore, the correct expression is 67\boxed{6^{-7}}, which corresponds to choice 2 in the given options.

Answer

67 6^{-7}

Exercise #11

Insert the corresponding expression:

1202= \frac{1}{20^2}=

Video Solution

Step-by-Step Solution

To solve this problem, we will use the properties of exponents. Specifically, we will convert the expression 1202 \frac{1}{20^2} into a form that uses a negative exponent. The general relationship is that 1an=an \frac{1}{a^n} = a^{-n} .

Applying this rule to the given expression:

  • Step 1: Identify the current form, which is 1202 \frac{1}{20^2} .
  • Step 2: Apply the negative exponent rule: 1202=202 \frac{1}{20^2} = 20^{-2} .
  • Step 3: This expression, 202 20^{-2} , represents 1202 \frac{1}{20^2} using a negative exponent.

Therefore, the expression 1202 \frac{1}{20^2} can be expressed as 202 20^{-2} , which aligns with choice 1.

Answer

202 20^{-2}

Exercise #12

724=? 7^{-24}=\text{?}

Video Solution

Step-by-Step Solution

Using the rules of negative exponents: how to raise a number to a negative exponent:

an=1an a^{-n}=\frac{1}{a^n} We apply it to the problem:

724=1724 7^{-24}=\frac{1}{7^{24}} Therefore, the correct answer is option D.

Answer

1724 \frac{1}{7^{24}}

Exercise #13

41=? 4^{-1}=\text{?}

Video Solution

Step-by-Step Solution

We begin by using the power rule of negative exponents.

an=1an a^{-n}=\frac{1}{a^n} We then apply it to the problem:

41=141=14 4^{-1}=\frac{1}{4^1}=\frac{1}{4} We can therefore deduce that the correct answer is option B.

Answer

14 \frac{1}{4}

Exercise #14

183=? \frac{1}{8^3}=\text{?}

Video Solution

Step-by-Step Solution

We use the negative exponent rule.

bn=1bn b^{-n}=\frac{1}{b^n}

We apply it to the problem in the opposite sense.:

183=83 \frac{1}{8^3}=8^{-3}

Therefore, the correct answer is option A.

Answer

83 8^{-3}

Exercise #15

129=? \frac{1}{2^9}=\text{?}

Video Solution

Step-by-Step Solution

We use the power property for a negative exponent:

an=1an a^{-n}=\frac{1}{a^n} We apply it to the given expression:

129=29 \frac{1}{2^9}=2^{-9}

Therefore, the correct answer is option A.

Answer

29 2^{-9}